Type the correct answer in the box. Use numerals instead of words. If necessary, use for the fraction bar. Simplify the expressi

Question

Type the correct answer in the box. Use numerals instead of words. If necessary, use for the fraction bar.

Simplify the expression.

4-8x+5) – (-33x – 26) =

NOX

in progress 0
Bella 2 weeks 2021-11-15T11:30:12+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-11-15T11:32:05+00:00

    Answer:

    x = -7/5

    Step-by-step explanation:

    Given the equation

    (4-8x+5) – (-33x – 26) = 0

    To get variable x, we will open the bracket first

    9-8x + 33x + 26 = 0

    35+25x = 0

    35 = -25x

    x = -35/25

    x = -7/5

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )